An optimal route selection with reinforcement learning for the waste management in Dhaka city - Rahman, Musfiqur (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.